PROSES KOMUNIKASI INTERPERSONAL DALAM LINGKUP PERPUSTAKAAN MELALUI MODEL KONSELING LAYANAN PEMUSTAKA - Mustofa, Muhamad Bisri; Silvia, Indah; Basyori, Ahmad (UIN Raden Intan Lampung, 2021)
As an institution, a library is charged with providing information in the form of books or collections that readers need. In addition to being a place of inguiry, they can also establish an interpersonal communication between officers and those who visit the library. In advanced development, libraries must also update the various connected elements within the library. Additionally, libraries should provide standardized services to support libraries. Bleaching services at the library can provide access for visitors to information, and the implementation of this services also involves interpersonal communication. Interpersonal communicationbetween visitors and the library can be applied through the update service counseling model. So with the update service counseling model, the library can khow which needs to be met in libraries and visitors can also find relevant information.